Biological and Clinical Effects of Calciprotein Particles on Chronic Kidney Disease-Mineral and Bone Disorder. (27th March 2018) - Akiyama, Kenichi; Kimura, Takaaki; Shiizaki, Kazuhiro
Abstract : Calciprotein particles (CPPs) are a new biological marker of chronic kidney disease-mineral and bone disorder (CKD-MBD). CPPs consist of phosphate, calcium, and some proteins, with phosphate being the major contributor to the level and biological activity of CPPs. Recent studies have shown the physiological and pathological significance of CPPs, including contributions to bone and mineral metabolism, and to tissue and organ impairments such as cardiovascular damage and inflammatory responses. These actions are well known as important aspects of CKD-MBD. Fibroblast growth factor 23 (FGF23), which is secreted from the bone as the phosphaturic hormone, is markedly elevated in CKD-MBD. Many clinical studies have shown significant relationships between the level of FGF23 and outcomes such as mortality, prevalence of cardiovascular disease, bone fracture, and levels of inflammatory markers. Basic and clinical studies have suggested that CPPs contribute to synthesis and secretion of FGF23. Surgical treatments such as renal transplantation and parathyroidectomy for patients with CKD-MBD suppress excess levels of phosphate, calcium, parathyroid hormone (PTH), and FGF23, which are related to the CPP level. Therefore, suppression of CPPs might also contribute to improved clinical outcomes after these treatments.